Health inequalities by gradients of access to water and sanitation between countries in the Americas, 1990 and 2010 - Oscar J. Mújica; Mariana Haeberer; Jordan Teague; Carlos Santos-Burgoa; Luiz Augusto Cassanha Galvão
OBJECTIVE: To explore distributional inequality of key health outcomes as determined by access coverage to water and sanitation (WS) between countries in the Region of the Americas. METHODS: An ecological study was designed to explore the magnitude and change-over-time of standard gap and gradient metrics of environmental inequalities in health at the country level in 1990 and 2010 among the 35 countries of the Americas. Access to drinking water and access to improved sanitation facilities were selected as equity stratifiers. Five dependent variables were: total and healthy life expectancies at birth, and infant, under-5, and maternal mortality. RESULTS: Access to WS correlated with survival and mortality, and strong gradients were seen in both 1990 and 2010. Higher WS access corresponded to higher life expectancy and healthy life expectancy and lower infant, under-5, and maternal mortality risks. Burden of life lost was unequally distributed, steadily concentrated among the most environmentally disadvantaged, who carried up to twice the burden than they would if WS were fairly distributed. Population averages in life expectancy and specific mortality improved, but whereas absolute inequalities decreased, relative inequalities remained mostly invariant. CONCLUSIONS: Even with the Region on track to meet MDG 7 on water and sanitation, large environmental gradients and health inequities among countries remain hidden by Regional averages. As the post-2015 development agenda unfolds, policies and actions focused on health equity-mainly on the most socially and environmentally deprived-will be needed in order to secure the right for universal access to water and sanitation.